ans. please

Asked by shobhitdc | 27th May, 2010, 04:09: PM

Expert Answer:

Dear Student,

 

Let the given polynomial is p(x) = 3x2 - ax + 5

Now, it is given that 2 is a zero of this polynomial.

So, p(2) = 0

or 3(2)2 - a(2) + 5 = 0

3 × 4 – 2a + 5 = 0

12 – 2a + 5 = 0

17 – 2a = 0

    2a = 17

Also b is a zero of p(x)

 

So, p(b) = 0

 

i.e.    3b2 – ab + 5 = 0

 

Substituting the value of a, we get

 

 

6b2 – 17b + 10 = 2 × 0 = 0

 

6b2 – 12b – 5b + 10 = 0

 

6b(b – 2) – 5(b – 2) = 0

 

(6b – 5)(b – 2) = 0

 

So, we get 6b – 5 = 0   or b – 2 = 0

 

 

Regards,

Team

Topper Learning

Answered by  | 27th May, 2010, 07:38: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.